Risk Factors for Posttracheostomy Tracheal Stenosis. (October 2018) - Li, Michael; Yiu, Yin; Merrill, Tyler; Yildiz, Vedat; deSilva, Brad; Matrka, Laura
Objective: To determine the incidence of posttracheostomy tracheal stenosis and to investigate variables related to the patient, hospitalization, or operation that may affect stenosis rates. Study Design: A combined retrospective cohort and case-control study. Setting: Tertiary care academic medical center. Subjects and Methods: A total of 1656 patients who underwent tracheostomy at a tertiary care medical center from January 2011 to November 2016 were reviewed for evidence of subsequent tracheal stenosis on airway endoscopy or computed tomography. Forty-three confirmed cases of posttracheostomy tracheal stenosis (PTTS) were compared with a subgroup of 319 controls. Factors including medical comorbidity, type and setting of tracheostomy, and hospitalization details were analyzed. Results: Five-year incidence of PTTS was 2.6%. Obesity was the sole demographic factor associated with stenosis. Hospitalization-related variables associated with stenosis included tracheostomy after 10 days of orotracheal intubation and endotracheal tube cuff pressure ≥30 mm H2 O. The surgical variables associated with higher rates of stenosis included percutaneous technique and insertion of an initial tracheostomy tube size >6. Bjork flap creation was negatively associated with stenosis. In multivariable analysis, obesity and insertion of tracheostomy tube size >6 were identified as risk factors. Conclusion: Greater than 10 days of orotracheal intubation prior to tracheostomy and endotracheal tube cuff pressure ≥30 mm H2 O were associated with greater rates of subsequent tracheal stenosis. The only patient-related factor associated with tracheal stenosis was obesity. Surgical variables associated with increased rates of subsequent stenosis included placement of a tracheostomy tube size >6, use of percutaneous technique, and failure to create a Bjork flap.